Clinical Characteristics and Profile of Heart Failure Patients at dr. Ramelan Navy Hospital in 2020 - I Kadek Herry Hermawan; Ken Christian Kawilarang; Febriyanti Hartono (Cardiovascular and Cardiometabolic Journal, 2022)
Background: Heart failure (HF) is a global pandemic affecting at least 26 million people worldwide and is increasing in prevalence. It has been associated with a high rate of readmissions and prolonged hospitalizations. There were few publications in Indonesia that described the characteristics and length of hospital stay of heart failure patients. Aims: To obtain data and describe the clinical characteristics and profile of heart failure patients hospitalized at dr. Ramelan Navy Hospital in 2020. Methods and Results: A cross sectional study was done using secondary data from patients’ medical records in dr. Ramelan Navy Hospital admitted during 2020. Data were then calculated and presented further. Based on the medical records, 121 heart failure patients were included in the study. Median age was 56 years old, 58,7% were men. Median length of stay was 6 days for all patients. 51.2% patients admitted to hospital with NYHA FC III. When patients were admitted to hospital, median systolic blood pressure was 124 mmHg and pulse was 91 beats per minute. Peripheral edema was shown in 67,8% of patients, hypertension in 49,6%, diabetes mellitus in 24,8%, ischemic heart disease in 52,9%. 6.6% of total patients treated in hospital died. Conclusion: Median length of stay for heart failure patients at dr. Ramelan Navy Hospital was 6 days. Most patients were men with median age of 56 years old. Keywords: Clinical characteristic, Demographic, Heart failure